2003
DOI: 10.1038/sj.onc.1206450
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation and cutaneous malignant melanoma

Abstract: Recent years have seen a steady rise in the incidence of cutaneous malignant melanoma worldwide. Although it is now appreciated that the key to understanding the process by which melanocytes are transformed into malignant melanoma lies in the interplay between genetic factors and the ultraviolet (UV) spectrum of sunlight, the nature of this relation has remained obscure. Recently, prospects for elucidating the molecular mechanisms underlying such gene-environment interactions have brightened considerably throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(210 citation statements)
references
References 174 publications
(153 reference statements)
3
197
0
10
Order By: Relevance
“…Ultraviolet (UV) radiation induces basal and squamous cell carcinoma and cutaneous malignant melanoma in humans [1][2][3] and is therefore a major environmental concern. UV radiations exert their toxic effects by causing DNA damage, which depends mainly on the wavelength.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet (UV) radiation induces basal and squamous cell carcinoma and cutaneous malignant melanoma in humans [1][2][3] and is therefore a major environmental concern. UV radiations exert their toxic effects by causing DNA damage, which depends mainly on the wavelength.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…In addition, to determine the relative toxicity of each wavelength tested, we quantified the viabilities of cells irradiated with the 4 different wavelengths at 100 mJ/cm 2 For determining the LD50 of the 4 tested wavelengths, we exposed PC12 cells to 25-800 mJ/cm 2 of 250-, 270-, and 290-nm radiations and to 125-8000 mJ/cm 2 of the 310-nm radiation.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…One new animal model reinforces epidemiological findings that childhood sunburn is a significant risk factor for developing melanoma. Noonan and colleagues found that a single high dose of UV radiation was sufficient to produce melanoma-like tumors in neonatal, but not adult, mice if the skin cells expressed a growth factor that stimulates melanocytes [19,20]. Chin and colleagues established a second elegant genetic model of murine melanoma in which the INK4a gene deletion cooperates with Ras overexpression [21].…”
Section: Uv Light and Melanomamentioning
confidence: 99%
“…These species are among the very few animals in which melanoma can be induced by UV alone. The Xiphophorus is also actively used as a genetic model organism for the study of neuroblastoma, retinoblastoma, and other malignancies; however, this system is ultimately limited by its evolutionary distance from mammals (62).…”
Section: Spalax P53 Favors Growth Arrest But Not Apoptotic Target Gementioning
confidence: 99%